Role of UV-B irradiation dose and intensity on color retention and antioxidant elicitation in broccoli florets (Brassica oleracea var. Italica) - Darré, Magalí (2017)
Postharvest UV exposure has been useful to i) delay senescence and ii) induce the accumulation of bioactive compounds in some vegetable species. However, no studies have been conducted to determine the treatment conditions (radiation dose and intensity) required to maximize these two diverse responses. In this work, we evaluated the effect of UV-B irradiation intensity (Control: 0, Low: 3.2, Medium: 4.0 and High: 5.0 W/m2) and dose (0, 2, 4, 8, 12 kJ/m2) on quality retention and antioxidant capacity of fresh broccoli florets during storage (4 °C for 17 days). Exposure to Low UV-B radiation and dose (2, 4 kJ/m2) reduced broccoli weight loss, delayed yellowing and improved chlorophyll and chlorophyllide retention. After long term storage, no marked improvement on the antioxidant capacity was found regardless of the irradiation condition. Evaluations at short time after UV-B exposure (0, 2, 6, 18 h) indicated that the treatments elicited antioxidant accumulation. Greatest antioxidant capacity was found in broccoli subjected to High intensity UV-B. Increased levels of aliphatic glucosinolates were found 18 h after the UV-B irradiation, whereas phenolic antioxidants peaked 6 h after the treatment. Results showed that Low UV-B doses and intensities delayed chlorophyll degradation and may be useful to complement refrigeration in fresh broccoli. Instead, High intensity UV-B exposure may be better suited as a pre-treatment to increase the antioxidant capacity prior to further processing such us freezing.